Age and "general health" - beside fracture classification - affect the therapeutic decision for geriatric pelvic ring fractures: a German pelvic injury register study - Höch, Andreas; Pieroh, Philipp; Gras, Florian; Hohmann, Tim; Märdian, Sven; Holmenschlager, Francis; Keil, Holger; Palm, Hans-Georg; Herath, Steven; Josten, Christoph; Schmal, Hagen; Stuby, Fabian (International orthopaedics, 2019)
Pelvic fracture, Fragility fracture, Pelvis, Treatment, Epidemiology
Gesehen am 30.04.2020